أثر التحول الرقمي على الأداء الوظيفي من وجهة نظر موظفي البلدية- د ا رسة حالة بلدية أولاد عدي لقبالة – ولاية المسيلة - لزهر فالي; مراد دغيمة (جامعة المسيلة, 2024)
تهدف الد ا رسة الى تحديد أثر التحول الرقمي بأبعاده الثلاثة ) الموارد البشرية، الهيكل التنظيمي، التكنولوجيا( على الأداء الوظيفي من وجهة نظر موظفي بلدية أولاد عدي لقبالة بالمسيلة، حيث اعتمدنا المنهج الوصفي في الد ا رسة النظرية، وتكون مجتمع الد ا رسة من جميع موظفي البلدية محل الد ا رسة، اختيرت عينة عشوائية مكونة من نسخة (spss) 30 موظفا، كما تم الاعتماد على الاستبيان كأداة رئيسية للوصول الى النتائج باستعمال برنامج 27 ، أهمها أن التحول الرقمي يؤثر على الأداء الوظيفي ،حيث يوجد أثر إيجابي للهيكل التنظيمي والتكنولوجيا على الأداء الوظيفي بينما لا أثر للموارد البشرية على الأداء الوظيفي، The study aims to determine the impact of digital transformation in its three dimensions (human resources, organizational structure, technology) on job performance from the point of view of employees of the municipality of Ouled Adi Qabalah in M’sila, where we adopted the descriptive approach in the theoretical study, and the study population consisted of all employees of the municipality under study. A random sample of 30 employees, and the questionnaire was relied upon as a main tool to reach the results, the most important of which is that digital transformation affects job performance, as there is a positive effect of the organizational structure and technology on job performance while there is no effect of human resources on job performance .
Keywords: التحول الرقمي، الأداء الوظيفي، بلدية أولاد عدي لقبالة ولاية المسيل ة; digital transformation; job performance; Ouled Addi guebala; M'Sila Province